Multistability and dynamic transitions of intracellular Min protein patterns. Issue 6 (8th June 2016) - Wu, Fabai; Halatek, Jacob; Reiter, Matthias; Kingma, Enzo; Frey, Erwin; Dekker, Cees
Abstract: Cells owe their internal organization to self‐organized protein patterns, which originate and adapt to growth and external stimuli via a process that is as complex as it is little understood. Here, we study the emergence, stability, and state transitions of multistable Min protein oscillation patterns in live Escherichia coli bacteria during growth up to defined large dimensions. De novo formation of patterns from homogenous starting conditions is observed and studied both experimentally and in simulations. A new theoretical approach is developed for probing pattern stability under perturbations. Quantitative experiments and simulations show that, once established, Min oscillations tolerate a large degree of intracellular heterogeneity, allowing distinctly different patterns to persist in different cells with the same geometry. Min patterns maintain their axes for hours in experiments, despite imperfections, expansion, and changes in cell shape during continuous cell growth. Transitions between multistable Min patterns are found to be rare events induced by strong intracellular perturbations. The instances of multistability studied here are the combined outcome of boundary growth and strongly nonlinear kinetics, which are characteristic of the reaction–diffusion patterns that pervade biology at many scales. Synopsis: Persistence and transitions of Min protein oscillations in diverse cell shapes reveal how reaction–diffusion patterns respond to cellular heterogeneity and boundary growth. Min protein oscillation patterns are analyzed in live Escherichia coli cells. Experiments and simulations show that multiple distinct Min patterns can be stable in different cells of the same shape. Pattern selection largely depends on the growth history of the cells. Theoretical analyses show that the observed multistability is not generic but relies on strong cooperative membrane binding. Abstract : Persistence and transitions of Min protein oscillations in diverse cell shapes reveal how reaction–diffusion patterns respond to cellular heterogeneity and fundary growth.